Smartphone Processor Architecture - Kohad, Hemlata; Ambhaikar, Asha (International Journal of Computer Sciences and Engineering, 2025)
Smartphone plays a crucial role in our daily life. Day by day there are advancements in technology which import changes in architecture of mobile phones. Low power, communication and performance largely affects the processor architecture of mobile phones. Processor architecture is now become complex to support the digital telephony. Mobile phones Processor design growing rapidly with respect to last generations . The objective of this paper is to overview the architecture of processor in Smart phones.